Los factores individuales, familiares e institucionales y su relación con la deserción estudiantil en el centro de formación artesanal nocturno Luz Hortensia Ruiz de la parroquia San Sebastián, cantón y provincia de Loja, periodo 2007– 2012 estrategias alternativas - Fernández Álvarez, Hugo Patricio (2015)
This research, called "individual factors, FAMILY AND INSTITUTIONAL AND ITS RELATIONSHIP WITH STUDENT DROP IN CRAFT NIGHT TRAINING CENTER" RUIZ HORTENSIA LIGHT "PARISH SAN SEBASTIAN, CANTON AND PROVINCE OF LOJA, PERIOD 2007- 2012 GUIDELINES ALTERNATIVE " I had as general objective: Reduce the dropout, the Craft Training Center Night" Hortensia Ruiz Luz "of San Sebastian, Canton and Parish Loja Province. The study was conducted under a mixed approach, with an ex post facto design and transversal. For the research process as applied methods: scientific, inductive, deductive, descriptive, analytical synthetic, accompanied by the technical; as observation, interview, which was conducted on the basis of instruments used as surveys, questionnaires, interview guides ,; surveys of the students of regular attendance and dropouts, interviews with family members. With regard to results, individual factors as found: Emigration from their homes to the city; romantic relationships in fact, lack of jobs. Among the family factors: Single Parent Family structure, family economy and parent education. And in regard to the institutional variables, the lag of the students, who are supported academically. inconsistent assessment processes; lack of academic assistance from teachers when entering classes; poor communication with mothers, parents and / or guardians. Based on the discussion of the results noted in conclusion that these factors have a direct relationship with the student desertion, for which the actions at the institutional level can be implemented in the craft center to decrease the rate of dropout object it is recommended study. Such recommendations should determine the identification of the general profile of the applicant income, developing the familiar diagnostic study. Monitoring and tutoring to parents identify support strategies. .. Prepare the family workup. Academic upgrading of teachers.